Aspects of design for manufacturability in RTM : design guidelines, composite mould design and early cost estimation - Veldsman, Gerhardus (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1995.